Adherence to multidomain interventions for dementia prevention: Data from the FINGER and MAPT trials. Issue 6 (29th April 2019) - Coley, Nicola; Ngandu, Tiia; Lehtisalo, Jenni; Soininen, Hilkka; Vellas, Bruno; Richard, Edo; Kivipelto, Miia; Andrieu, Sandrine; ,
Abstract: Introduction: Multidomain interventions, targeting multiple risk factors simultaneously, could be effective dementia prevention strategies, but may be burdensome and not universally acceptable. Methods: We studied adherence rates and predictors in the Finnish Geriatric Intervevntion Study to Prevent Cognitive Impairment and Disability and Multidomain Alzheimer Preventive Trial prevention trials, for all intervention components (separately and simultaneously). Finnish Geriatric Intervevntion Study to Prevent Cognitive Impairment and Disability participants received a 2‐year multidomain lifestyle intervention (physical training, cognitive training, nutritional counseling, and cardiovascular monitoring). Multidomain Alzheimer Preventive Trial participants received a 3‐year multidomain lifestyle intervention (cognitive training, physical activity counseling, and nutritional counseling) with either an omega‐3 supplement or placebo. Results: Adherence decreased with increasing intervention complexity and intensity: it was highest for cardiovascular monitoring, nutritional counseling, and the omega‐3 supplement, and lowest for unsupervised computer‐based cognitive training. The most consistent baseline predictors of adherence were smoking and depressive symptoms. Discussion: Reducing participant burden, while ensuring that technological tools are suitable for older individuals, maintaining face‐to‐face contacts, and taking into account participant characteristics may increase adherence in future trials.